A Novel Ex Vivo Model to Investigate the Underlying Mechanisms in Alzheimer’s Disease - Brai, Emanuele; Stuart, Skye; Badin, Antoine-Scott; Greenfield, Susan A. (Frontiers in Cellular Neuroscience, 2017)
Currently there is no widely accepted animal model reproducing the full pathological profile of Alzheimer’s disease (AD), since the basic mechanisms of neurodegeneration are still poorly understood. We have proposed that the interaction between the α7 nicotinic acetylcholine receptor (α7-nAChR) and a recently discovered toxic peptide, cleaved from the acetylcholinesterase (AChE) C-terminus, could account for the aberrant processes occurring in AD. In this paper we describe a new application on ex-vivo model procedure, which combines the advantages of both in-vivo and in-vitro preparations, to study the effects of the AChE-derived peptide on the rat basal forebrain (BF). Western blot analysis showed that the levels of α7-nAChR, p-Tau and Aβ are differentially expressed upon the AChE-peptide administration, in a selective site-dependent manner. In conclusion, this methodology demonstrates the action of a novel peptide in triggering an AD-like phenotype and proposes a new ex-vivo approach for manipulating and monitoring neurochemical processes contributing to neurodegeneration, in a time-dependent and site-specific manner.